PENGARUH FAKTOR-FAKTOR TRAINING PROGRAM TERHADAP PRESTASI KERJA KARYAWAN HOTEL SATELIT SURABAYA - Sumarno (Fakultas Ekonomi Universitas 45 Surabaya, 2013)
Attitude of Growth of world parawisata specially, effort hotel service progressively day show the emulation and growth more and more fast to face the the growth of management of Satellite Hotel put the a profound interest to development of human resource of through program training for all employees with an eye to improve the knowledge and skilled in executing its work duty so that through program of training of labour capacity of employees can be improved in the end give the big benefit to company target. This Research target first of all to know more detail from training program consisted of by the factors of coach ability, training items, training method, training competitor, facility of training and komitmen leader. Whether collectively have the influence having a meaning of to labour capacity of employees of part of operational of at Satellite Hotel. Second anticipated by that factor of komitmen leader have the dominant influence to labour capacity of employees of part of operational at Hotel of Satellite Surabaya. In this research is population of taken as focus in research is employees of part of operational as much 106 employees people, sampel research conducted with the amount 53 people ( 50 %) deputizing employees of part of operational of research instrument to obtain ;get the data used to measure the factors program the training use the enquette which is passed to employees and leader by using Technique Analyse the doubled linear regresi. Analyse the data use the computer program the SPSS with the technique analyse the test simultan, test the parsial, test the classic assumption, its examination is relied on by level signifikasi 5 %.